2018
DOI: 10.3389/fpsyg.2018.00842
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mild Cognitive Impairment on the Event-Related Brain Potential Components Elicited in Executive Control Tasks

Abstract: We summarize here the findings of several studies in which we analyzed the event-related brain potentials (ERPs) elicited in participants with mild cognitive impairment (MCI) and in healthy controls during performance of executive tasks. The objective of these studies was to investigate the neural functioning associated with executive processes in MCI. With this aim, we recorded the brain electrical activity generated in response to stimuli in three executive control tasks (Stroop, Simon, and Go/NoGo) adapted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 81 publications
(95 reference statements)
3
14
0
Order By: Relevance
“…Beyond individual differences, working memory becomes less efficient during healthy ageing (Park et al, 2002;Peich et al, 2013), and it is drastically compromised in AD patients (Kirova et al, 2015). Interestingly, the brain of healthy elderly subjects deploys compensatory mechanisms (e.g., increased frontal activity and more bilateral patterns of activation during the performance of cognitive tasks) to maintain a good cognitive functioning (Davis et al, 2012) and the loss of this compensatory capacity is strongly related to cognitive impairment in AD patients (Cespón et al, 2018).…”
Section: Cognitive Impairment During Physiological and Pathological Amentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond individual differences, working memory becomes less efficient during healthy ageing (Park et al, 2002;Peich et al, 2013), and it is drastically compromised in AD patients (Kirova et al, 2015). Interestingly, the brain of healthy elderly subjects deploys compensatory mechanisms (e.g., increased frontal activity and more bilateral patterns of activation during the performance of cognitive tasks) to maintain a good cognitive functioning (Davis et al, 2012) and the loss of this compensatory capacity is strongly related to cognitive impairment in AD patients (Cespón et al, 2018).…”
Section: Cognitive Impairment During Physiological and Pathological Amentioning
confidence: 99%
“…latency is delayed by physiological and pathological ageing whereas the frontal P300 amplitude is usually increased in healthy elderly (which is thought to reflect brain compensatory mechanisms) and decreased in AD patients (Polich and Corey-Bloom, 2005;Rossini et al, 2007), which may be reflecting a loss of the compensatory capabilities. Crucially, studying electrophysiological correlates of working memory processes before and after applying tDCS may provide important insights about the more appropriate parameters -such as polarity-to be used for "enhancing" the neural processes related to improved cognitive performance (Cespón et al, 2018). Improved working memory performance after anodal tDCS in healthy young (Keeser et al, 2011) and elderly subjects (Cespón et al, 2017) has been related to an increased frontal P300.…”
Section: Electrophysiological Correlates Of Working Memorymentioning
confidence: 99%
“…The event-related brain potentials (ERPs) technique is an appropriate tool to obtain brain correlates of the cognitive processes taking place during the performance of a cognitive task due to its high temporal resolution. In addition, previous studies suggested that ERP modulations are more sensitive than behavioral measures to incipient physiological processes related to pathological aging (Zurrón et al, 2018 ). In the present study, executive control functions will be investigated in samples of healthy elderly participants divided in low SMC (LSMC) and high SMC (HSMC) groups.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of traditional tests that have been digitized are reaction speed tests, continuous performance tests, and card sorting tests. Examples of paradigms that have been imported from cognitive science for clinical applications are the Simon task (Craft & Simon, 1970;Simon & Small, 1969;Zurron et al, 2018), the Stop-signal task (Logan, Cowan, & Davis, 1984;Nigg, 2017), and the Flanker task (Eriksen & Eriksen, 1974;Zelazo et al, 2014).…”
Section: Psychometric Obstaclesmentioning
confidence: 99%